Hubungan Internasional Indonesia dan Uni Eropa Terhadap Kebijakan Ekspor Nikel Sebagai Tantangan Perekonomian - Khafidhotul Ilmi; Dyah Estu Kurniawati; Haryo Prasodjo (Journal of Business and Economics Research (JBE), 2022)
One of the problems in international relations occurred due to international trade which led to the European Union's feud against Indonesia on January 17, 2018 in which the European Parliament made a decision on the use of palm oil for biodiesel products. The decision was made to increase energy efficiency to 35% by 2030, most parliaments approved the plan to ban the use of palm oil as the main raw material in biodiesel in 2021, seeing this the Government of Indonesia through the Ministry of Energy and Mineral Resources (ESDM) starting January 1, 2020, a ban on the export of nickel ore or nickel ore will be imposed. The decision was made in an effort to maintain nickel reserves by considering the sustainability of the supply of raw materials from existing smelters. This research was conducted using descriptive quantitative methods with a literature/literature study approach and was descriptive. The results of this study conclude that bilateral international relations between Indonesia and the European Union are very tight, this is indicated by the existence of trade problems and the existence of a lawsuit to the WTO from the European Union against Indonesia. to increase State spending, improve trade relations between Indonesia and the European Union with consideration of tax relief, implementation of guidance for exporters/MSMEs who will export their products. The WTO in resolving disputes between its members has a system that is in many ways unique and successful